FILOSOFI EKONOMI MENURUT PANDANGAN ISLAM - Ridha, Sovia (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2014)
Humans being is the leader (khalifah) of Allah on earth. As a leader, every single man is demanded to be obedient to the rules made by the God. These rules have been described in His Book, Koran, and in His Prophetâ€™ hadith. One of the humanâ€™s obediance forms to God is by keeping the relationship with the Creator or it is known with the term â€œhablul minallahâ€and also by maintaining his relationship with other people which is known as â€œhabl min alÂnasâ€. All forms of human activities either related to worship (mahdhah or ghairu mahdhah) or muamalah activities concerning with economic activities cannot be separated from the eyes of Allah. Therefore one of the economic philosophy keys of Islam is selfÂsurrender to the Creator in every behavior. In addition, human is also required to maintain good relations with fellow creatures of Allah such as to the other human being, animals, plants, and even the environment. To be fair and to avoid oppression toward other creatures are examples of human respect forms to the creatures of Allah SWT.